Assessment of relationship between oral health behavior, oral hygiene and gingival status of dental students - Afsheen Lalani; Pralhad L Dasar; N Sandesh; Prashant Mishra; Sandeep Kumar; Swati Balsaraf (Wolters Kluwer Medknow Publications, 2015)
Background: The behavior of oral health providers toward their own oral health reflects their understanding of the importance of preventive dental procedures and of improving the oral health of their target population. Aim: This study was done with an aim to assess the relationship between oral health behavior, oral hygiene and gingival status of third and final year dental students from a Dental College in Indore City, India. Methods: A total of 137 dental students participated in the study. The students were invited to complete the Hiroshima University-Dental Behavioral Inventory (HU-DBI) questionnaire. The HU-DBI questionnaire consisted of twenty polar responses (agree/disagree) regarding oral health-related behavior. In addition, two further questions about the frequency of brushing and flossing were included. Subsequently, oral health examination was conducted to assess plaque and gingival status. Data were analyzed using Chi-square test, Independent sample t-test, and Pearson's correlation. The significance level was set at P ≤ 0.05. Result: The results showed that about 66.6% of the students checked their teeth in the mirror after brushing. Only 20.1% of the students reported bleeding from gums. The mean oral heath behavior score (HU-DBI) was 6.47 ± 2.0. A negative correlation of HU-DBI scores with plaque (r = −0.501) and gingival scores (r = −0.580) was observed. Conclusion: Thus, it is concluded that there is a significant relationship between the oral health behavior, oral hygiene, and gingival status of dental students. Dental students with better self-reported oral health behavior had lower plaque and gingival scores indicating a better attitude toward oral health.